2019
DOI: 10.15616/bsl.2019.25.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Metformin on Neuro-inflammation and NLRP3 Inflammasome Activation in BV-2 Microglial Cells

Abstract: Metformin is a drug used for the treatment of diabetes and is associated with anti-inflammatory reaction, but the underlying mechanism is unclear. In this study, we investigated the effect of metformin on the inflammatory response in BV-2 microglial cells induced by lipopolysaccharide (LPS) and S100 calcium-binding protein A8 (S100A8). The results revealed that metformin significantly attenuated several inflammatory responses in BV-2 microglial cells, including the secretion of pro-inflammatory cytokines, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“… 28 , 63 , 65 Importantly, metformin preTx has been shown to reduce in vivo microgliosis, NF-κB activity, and levels of tumor necrosis factor alpha (TNF-α), IL-6, and IL-1β in a rodent stroke model, 43 as well as in vitro microglial secretion of TNF-α and IL-6 in the presence of lipopolysaccharide or S100 calcium-binding protein A8. 66 , 67 Thus, understanding the specific factor(s) that regulate NSC behavior has important implications for neuro-regenerative strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 63 , 65 Importantly, metformin preTx has been shown to reduce in vivo microgliosis, NF-κB activity, and levels of tumor necrosis factor alpha (TNF-α), IL-6, and IL-1β in a rodent stroke model, 43 as well as in vitro microglial secretion of TNF-α and IL-6 in the presence of lipopolysaccharide or S100 calcium-binding protein A8. 66 , 67 Thus, understanding the specific factor(s) that regulate NSC behavior has important implications for neuro-regenerative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This way of western blot analysis is well accepted and reliable one. Researchers usually present the relative expression in their test samples either in ratio of control (at the scale of 1) [3638] or percent of control (at the scale of 100) [3943]. We have been presenting our western data in previous lab publications in this pattern [27, 28, 32, 33, 44].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that metformin decreases the levels of IL-1β and IL-6 in APP/PS1 mice [76]. In addition, different studies have highlighted the anti-inflammatory and antioxidant function of metformin, with several pathways playing a key role in the activation of AMPK [147][148][149][150][151][152]. In certain cases, metformin suppresses inflammation and decreases or removes inflammatory factors largely by dependent pathways and often independently of AMPK at the cellular level and elsewhere at the systemic level [148,149].…”
Section: Metformin Effects On Neuroinflammationmentioning
confidence: 99%
“…According to Ha and colleagues, metformin possesses anti-inflammatory effects [ 147 ]. The neuroinflammatory response requires microglial cells, which are resident phagocytes in the CNS.…”
Section: Molecular Mechanism Involved In Neuroprotective Effects Of Metformin In Alzheimer’s Diseasementioning
confidence: 99%